3-Dimensional Retraction Spring for Buccally Impacted Canines. Issue 4 (October 2021) - Verma, Sanjeev; Bhupali, Nameksh Raj; Singh, Satinder Pal
An innovative method to successfully erupt buccally impacted canines in difficult positions, that is, sector III and IV mesial to the root of lateral incisors into occlusion, has been described. 3-dimensional retraction spring is fabricated using 0.017 × 0.025-inch Titanium Molybdenum Alloy(TMA) wire and 45-degree bends are made simultaneously in 2 directions. The first bend is given distally starting from mesial of the first premolar and the second buccally at the same location. This 3-dimensional spring with its unique design provides the required labial and distal force with least chances of root resorption. A representative case is illustrated to demonstrate the clinical use of the same.